Draft Annual Plan 1972-73 - Planning Commission (Planning Commission, 1972)
Community Development Panchayats Multipurpose Projects Major and Medium Irrigation Anti-waterlogging. Drainage and Flood Control Power Projects Industries Roads Road Transport Civil Aviation Tourism General Education Technical Education Industrial Training Health Water Supply
Statistical Statements Planning Department Punjab